(untitled) (Scientific journal of the Fergana State University, 2024)
this article shows the ideological, ideological and informational forms of threats to public safety, based on the analysis of modern social philosophical and political concepts, the social need to ensure public safety, the prevention of threats against it, and the social contract based on the mechanisms of social consensus in their elimination. , the philosophical aspects of establishing agreement, compromise and cooperation are analyzed